2017
DOI: 10.3917/enf1.171.0061
|View full text |Cite
|
Sign up to set email alerts
|

Bien-être perçu, performances scolaires et qualité de vie des enfants à l’école et au collège : étude longitudinale

Abstract: Cette étude vise à décrire différents profils de bien-être à l’école et au collège et à déterminer si ces profils sont associés aux performances académiques, à la satisfaction scolaire et à la qualité de vie globale des élèves évaluées un an plus tard. Pour cela, 557 élèves scolarisés à l’école primaire (N = 253) et au collège (N = 354) ont été suivis pendant deux années scolaires. Les analyses réalisées ont permis de distinguer 3 profils de bien-être à partir des scores obtenus aux différentes dimensions du q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…As expected, I found that schools' SES does not have a significant impact on children's overall positive explicit perception of school. This result is coherent with previous works showing that self-reported, explicit school satisfaction is unrelated or at best modestly related to children's SES or to the average SES of their school (Bacro et al, 2017;Baker and Maupin, 2009;Elmore and Huebner, 2010). To the contrary, using a specifically designed Implicit Association Test, I did find a significant effect of schools' SES on children's implicit school satisfaction.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…As expected, I found that schools' SES does not have a significant impact on children's overall positive explicit perception of school. This result is coherent with previous works showing that self-reported, explicit school satisfaction is unrelated or at best modestly related to children's SES or to the average SES of their school (Bacro et al, 2017;Baker and Maupin, 2009;Elmore and Huebner, 2010). To the contrary, using a specifically designed Implicit Association Test, I did find a significant effect of schools' SES on children's implicit school satisfaction.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the fact that children attending medium-SES schools are more positively disposed toward school than those attending low-SES schools corroborates Bourdieu and Passeron's hypothesis (1964;1970) according to which habitus of students from medium-and high-SES backgrounds are more favorable to school success than those of low-SES students. Previous studies have indeed established a link between positive perception of school and high academic performance (e.g., Bacro et al, 2017;Fenouillet et al, 2014;Suldo et al, 2006).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations